Phytochemical, antioxidant and protective effect of cactus cladodes extract against lithium-induced liver injury in rats. (1st January 2017) - Ben Saad, Anouar; Dalel, Brahmi; Rjeibi, Ilhem; Smida, Amani; Ncib, Sana; Zouari, Nacim; Zourgui, Lazhar
Abstract: Context: Opuntia ficus-indica (L.) Mill. (Castaceae) (cactus) is used in Tunisian medicine for the treatment of various diseases. Objective: This study determines phytochemical composition of cactus cladode extract (CCE). It also investigates antioxidant activity and hepatoprotective potential of CCE against lithium carbonate (Li2 CO3 )-induced liver injury in rats. Materials and methods: Twenty-four Wistar male rats were divided into four groups of six each: a control group given distilled water (0.5 mL/100 g b.w.; i.p.), a group injected with Li2 CO3 (25 mg/kg b.w.; i.p.; corresponding to 30% of the LD50 ) twice daily for 30 days, a group receiving only CCE at 100 mg/kg of b.w. for 60 days and then injected with distilled water during the last 30 days of CCE treatment, and a group receiving CCE and then injected with Li2 CO3 during the last 30 days of CCE treatment. The bioactive components containing the CCE were identified using chemical assays. Results: Treatment with Li2 CO3 caused a significant change of some haematological parameters including red blood cells (RBC), white blood cells (WBC), haemoglobin content (Hb), haematocrit (Ht) and mean corpuscular volume (VCM) compared to the control group. Moreover, significant increases in the levels of glucose, cholesterol, triglycerides and of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) activities were observed in the blood of Li2 CO3 -treated rats. Furthermore, exposure to Li2 CO3 significantly increased the LPO level and decreased superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) activities in the hepatic tissues. Conclusion: CCE possesses a significant hepatoprotective effect.